That's not my zebra its mane is too furry - Watt, Fiona; Wells, Rachel (London usborne publishing, 2014)
This delightful series of board books is aimed at very young children. The bright pictures, with their patches of different textures, are designed to develop sensory and language awareness. Babies and toddlers will love turning the pages and touching the feely patches
Scientific notions
1 13
Keywords: Science